Integrated Management of Bacterial Spot on Tomato in Florida - Tim Momol; Jeff Jones; Steve Olson; Aleksa Obradovic; Botond Balogh; Paula King (EDIS)
This document is Fact Sheet PP110, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published September 2002.